Hubungan antara Tingkat Kecemasan dengan Kualitas Hidup Pasien Stroke di Semarang - Nur Hidayah Nur Hidayah; Dwi Heppy Rochmawati; Wigyo Susanto (NAJ Nursing Applied Journal, 2025)
Stroke is one of the leading causes of disability, resulting in a decline in the quality of life of its sufferers. In addition to physical impairments, stroke patients often experience anxiety, which can hinder the recovery process and lower overall quality of life. This study aims to analyze the relationship between anxiety levels and the quality of life of stroke patients. The research design used a correlational descriptive approach with a cross-sectional method. The study population consisted of stroke patients receiving care or rehabilitation in healthcare facilities, with a total sampling technique for sampling. The research instruments included an anxiety questionnaire and a quality of life questionnaire. Data analysis was performed using Somers’ d statistical test. The results showed that most stroke patients experienced moderate anxiety and had low quality of life. The Somers’ d test indicated a significant relationship between anxiety and the quality of life of stroke patients (p < 0.05). These findings suggest that the higher the anxiety level, the lower the quality of life perceived by the patients. Therefore, healthcare providers are expected to not only focus on physical therapy but also provide psychological interventions to reduce anxiety, thus improving the quality of life of stroke patients.